2018
DOI: 10.1002/lno.10814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nitrogen availability upon the electron requirement for carbon fixation in Australian coastal phytoplankton communities

Abstract: Nitrogen (N) availability affects phytoplankton photosynthetic performance and regulates marine primary production (MPP) across the global coast and oceans. Bio‐optical tools including Fast Repetition Rate fluorometry (FRRf) are particularly well suited to examine MPP variability in coastal regions subjected to dynamic spatio‐temporal fluctuations in nutrient availability. FRRf determines photosynthesis as an electron transport rate through Photosystem II (ETRPSII), requiring knowledge of an additional paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 112 publications
(291 reference statements)
5
75
0
1
Order By: Relevance
“…High excitation pressure also triggers the upregulation of heat dissipation mechanisms in the pigment antenna (here estimated as NPQNSV), and several studies have reported a correlation between Φe,C and NPQNSV (Hughes et al, 2018a;Schuback et al, 2015Schuback et al, , 2016bSchuback et al, , 2017aZhu et al, 2017). We observed such a correlation at both of our sampling sites (Fig.…”
Section: The Electron Requirement For Carbon Fixation φEcsupporting
confidence: 71%
“…High excitation pressure also triggers the upregulation of heat dissipation mechanisms in the pigment antenna (here estimated as NPQNSV), and several studies have reported a correlation between Φe,C and NPQNSV (Hughes et al, 2018a;Schuback et al, 2015Schuback et al, , 2016bSchuback et al, , 2017aZhu et al, 2017). We observed such a correlation at both of our sampling sites (Fig.…”
Section: The Electron Requirement For Carbon Fixation φEcsupporting
confidence: 71%
“…Where nutrients are limiting at higher temperatures there may also be an increased uncoupling between the light and dark reactions of photosynthesis as energy and reductant is used in nutrient uptake and cellular maintenance rather than carbon fixation (Hughes et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…However, temperature did not show any significant correlation with other variables except Φ e,CC and K PAR . The effect of temperature on Φ e,C may be indirect, as it reflects the state of stratification, which in turn modulates nutrient supply and light availability in the upper layer (Mousing et al 2014, Hughes et al 2018. The negative correlation of temperature with nutrients, K PAR , and chl a supports this interpretation, although only the correlation with K PAR was significant.…”
Section: Relationship Between φ Ec and Environmental Variablesmentioning
confidence: 91%